2013
DOI: 10.1002/adsc.201300301
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Biooxidation of Racemic trans‐Cyclic Vicinal Diols: One‐Pot Synthesis of Both Enantiopure (S,S)‐Cyclic Vicinal Diols and (R)‐α‐Hydroxy Ketones

Abstract: Highly regio‐ and enantioselective alcohol dehydrogenases BDHA (2,3‐butanediol dehydrogenase from Bacillus subtilis BGSC1A1), CDDHPm (cyclic diol dehydrogenase from Pseudomonas medocina TA5), and CDDHRh (cyclic diol dehydrogenase from Rhodococcus sp. Moj‐3449) were discovered for the oxidation of racemic trans‐cyclic vicinal diols. Recombinant Escherichia coli expressing BDHA was engineered as an efficient whole‐cell biocatalyst for the oxidation of (±)‐1,2‐cyclopentanediol, 1,2‐cyclohexanediol, 1,2‐cyclohepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…A recent report convincingly demonstrated the value of bacterial trans‐ diol dehydrogenase enzymes, as biocatalysts for the stereoselective dehydrogenation of cyclic vicinal trans ‐diols and formation of chiral α‐ketols 10e. A complementary study of stereoselectivity, observed during cis ‐diol dehydrogenase‐catalysed dehydrogenation of cyclic vicinal cis ‐diols and formation of chiral α‐ketols, is presented herein.…”
Section: Introductionmentioning
confidence: 79%
“…A recent report convincingly demonstrated the value of bacterial trans‐ diol dehydrogenase enzymes, as biocatalysts for the stereoselective dehydrogenation of cyclic vicinal trans ‐diols and formation of chiral α‐ketols 10e. A complementary study of stereoselectivity, observed during cis ‐diol dehydrogenase‐catalysed dehydrogenation of cyclic vicinal cis ‐diols and formation of chiral α‐ketols, is presented herein.…”
Section: Introductionmentioning
confidence: 79%
“…The conversion and ee value of 2‐hydroxycyclopentanone ( 2 a ) and 2‐hydroxycyclohexanone ( 2 b ) were determined by GC analysis. The absolute configuration was determined by comparing the relative retention times of the reference (Table S6 in the Supporting Information) …”
Section: Methodsmentioning
confidence: 99%
“…reported the conversion of cyclohexane, cyclohexanol or cyclohexanone through three steps, two steps or one step to form 2‐hydroxycyclohexanone ( 2 b ) using P450‐BM3 monooxygenase from Bacillus megaterium . Alcohol dehydrogenases BDHA (2,3‐butanediol dehydrogenase from Bacillus subtilis BGSC1 A1) was engineered as an efficient biocatalyst for the stereoselective oxidation of 1,2‐cyclopentanediol ( 3 a ) and 1,2‐cyclohexanediol ( 3 b ) to the corresponding cyclic ( R )‐α‐hydroxy ketones …”
Section: Introductionmentioning
confidence: 99%
“…[213] After SpEH-mediated epoxide hydrolysis, NAD + + -dependent dehydrogenase oxidizes the diol to the ketone ( Figure 22). Interestingly,t wo different en- Different from the earlier established system using LDH, [214] the whole-cell catalyst was constructed by the co-transformation of pETDuet-1/SpEH-NOX and pET28a/BDHA.A sb oth plasmidss hare the same ORI, plasmid maintenance exclusively relied on the selection by two different antibiotics.T his is in contrast to the concept of plasmid incompatibility and might result in inconsistent expression patterns in different cell populations.…”
Section: M Icrobialcell Factories Conducting Optimized Redox Cascadesmentioning
confidence: 99%
“…Different from the earlier established system using LDH,214 the whole‐cell catalyst was constructed by the co‐transformation of pETDuet‐1/ SpEH ‐NOX and pET28a/ BDHA . As both plasmids share the same ORI, plasmid maintenance exclusively relied on the selection by two different antibiotics.…”
Section: Microbial Cell Factories Conducting Optimized Redox Cascadesmentioning
confidence: 99%